Below ground food producing plants and their contribution to the world food kitty – A review - PRASAD, RAJENDRA; SHIVAY, YASHBIR SINGH (The Indian Journal of Agricultural Sciences, 2021)
Below ground crops in general are regarded as the Treasures in the soil in view of their very high-yield potentialwhich in turn is hidden inside the soil. Taking into account the potentialities of below ground crops under the presentscenario of global environmental change, these crops can be regarded as the Future crops for the millennium. Belowground crops are the most important land-grown food crops after cereals and grain legumes. They are either thestaple or subsidiary food for large share of the human population, mostly in the developing countries of the tropicsor sub-tropics and even in the temperate climatic conditions. In spite of the fact that below ground foods contributesubstantially to the world food needs but it is not well recognized. Potato is the fourth major supplier of carbohydratesafter wheat, rice, and maize and in many countries; cassava is a major food for the poor households especially in Africancountries. Groundnut is a major oilseed in India. What is not recognized is its contribution to meeting the proteinneeds of the people. Below-ground root crops meet about 30% energy needs of people in some African countries.Hence, below ground food-producing crops contribute significantly to the world food and energy requirements andneed to be promoted for further their share through basic and applied research.